EKSISTENSI OTONOMI DESA PAKRAMAN PADA MASYARAKAT ADAT DI BALI - Yudhi Pramana, Kadek; Oka Parwata, A A Gede; Ari Atu Dewi, A A Istri (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 05, Oktober 2014, 2014)
Desa Pakraman is one example of partnership law in Indonesia since the inception of theinherent right of autonomous (the right to manage his own household). Desa Pakraman’sexistence in Bali, in fact coexist with the village government offices. On the other handPakraman is part of the legal order of the country that should be subject to the laws of the Stateregulations. It is, raises fundamental issues related to the presence of Pakraman autonomywithin the national legal system. Based on the background of the problem can be formulated asfollows 1 ) What are the elements of autonomy Desa Pakraman, 2), How does the existence ofjuridical autonomy of Desa Pakraman. The Juridical based is used to dissect the problem,namely: Desa Pakraman’s concept and the concept of autonomy.The method is method of normative research approach legislation, concepts andanalytical approaches. Discussion of the problem is that the elements of Desa Pakraman’s autonomy are: 1) The power set of legal rules, 2) The power to organize the life of theorganization. 3) Power resolve legal issues. While the existence of Desa Pakraman’s juridicalautonomy clearly regulated in Pasal 18 b Ayat (2) UUD NRI 1945, Pasal 3 UUPA , Pasal 6 ayat(1), Pasal 6 ayat (2) dan Peraturan Daeran nomor 3 Taun 2001 yang telah diubah denganPerda Nomor 3 Tahun 2003 tentang Desa Pakraman, yaitu Pasal 5 huruf a dan b, Pasal 6 hurufa, dan Pasal 7 ayat (1).
Keywords: Existence, autonomy, Desa Pakraman, indigenous peoples